Equity Carve-Outs and Managerial Discretion - Allen, Jeffrey W.; McConnell, John J. (Journal of Finance, 1998)
This study proposes a managerial discretion hypothesis of equity carve-outs in which managers value control over assets and are reluctant to carve out subsidiaries. Thus, managers undertake carve-outs only when the firm is capital constrained. Consistent with this hypothesis, firms that carve out subsidiaries exhibit poor operating performance and high leverage prior to carve-outs. Also consistent with this hypothesis, in carve-outs wherein funds raised are used to pay down debt, the average excess stock return of + 6.63 percent is significantly greater than the average excess stock return of −0.01 percent for carve-outs wherein funds are retained for investment purposes.